A NOVEL METOD OF SYNTHESIS OF THE 4Н,10Н-PYRANO[2,3-f]CHROMEN-4,10-DIONE SYSTEM (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
A simple and efficient method for the synthesis of 4Н,10Н-pyrano[2,3-f]chromen-4,10-dione system, which is characterized by rather high yieldson relatively mild conditions was offered. Design of that system has been carried out by annelation of γ-pirone cycle to chromone core. 4Н,10Н-Pyrano[2,3-f]chromen-4,10-dione system was elaborated using 8-(3-dimethylamino-2-propenoyl)-7-hydroxy-4H-chromen-4-one cyclization in aceticacid. The starting enaminoketone derivative was synthesized in two stages from 7-acetoxychromone. 3-(4-Chlorophenyl)-6-ethyl-2-methyl-4-oxo-4H-7-chromenyl acetate was converted into 8-acetyl-3-(4-chlorophenyl)-6-ethyl-7-hydroxy-2-methyl-4H-4-chromenone by Frice rearrangement. Subsequentheating of the latter with N,N-dimethylformamide dimethyl acetal in toluene gave the desired 3-(4-chlorophenyl)-8-(3-dimethylamino-2-propenoyl)-6-ethyl-7-hydroxy-4H-chromen-4-one. The advantage of such approach is the ability to obtain biopotent systems with different substituentsin pyrone cycles, that will contribute to the search for new biologically active compounds. The structures of synthesized compounds havebeen assigned on the basis of analytical and spectra data.
Keywords: 8-acethyl-7-hydroxychromones, 8-(3-dimethylamino-2-propenoyl)-7-hydroxychromones, N,N-dimethylformamide dimethyl acetal, 4Н,10Нpyrano[2,3-f]chromen-4,10-diones.